Posture and balance in elderly practicers and non-practicers of physical exercises - Bianchi, Adriane Behring; Antunes, Mateus Dias; Santos, Natália Quevedo dos; Bulla, Henrique Augusto; Silva, Eraldo Schunk; Marques, Amélia Pasqual; Bertolini, Sonia Maria Marques Gomes (Journal of Physical Education (Maringá), 2020)
This study aimed at comparing body posture and balance between practicing and non-exercising elderly. This is a cross-sectional and analytical study, with a convenience sample of 245 elderly people, the group of physical exercise practitioners (GP) ) (n = 169) and non-physical exercise group (NGP) (n = 76). The balance was evaluated by the Berg scale and the orthostatic body posture through SAPO software and the posture seated by the Rocha e Souza protocol. It was found that the elderly of the GP had better seated posture (p = 0.046), vertical alignment of the right trunk (p = 0.039), vertical alignment of the right (p = 0.027) and left (p = 0.004), left ankle (p = 0.023), asymmetry of frontal plane (p = 0.008) and balance (p = 0.001), compared to the elderly of GNP. It is concluded that the elderly who practice physical exercises present better posture and balance, compared to non-practitioners. This information can be useful to increase and encourage programs of physical practices and physical activities for the elderly in Brazil.